Kompetensi Komunikasi Antarbudaya dalam Pembelajaran Bahasa Inggris: Analisis Kesenjangan Antara Kurikulum, Buku Teks, dan Praktik Kelas di SMA Indonesia - Aisyah Aulia Putri; Nurasia Natsir (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Intercultural Communicative Competence (ICC) has become a key objective of English language education; however, its implementation in Indonesia remains insufficiently understood. This study investigates the alignment between ICC expectations in the Kurikulum Merdeka, English textbooks, and classroom practices in Indonesian senior high schools. An exploratory sequential mixed methods design was employed, involving document analysis of four government-issued English textbooks for grades X–XII, classroom observations in 15 schools across three provinces, a survey of 87 English teachers, and in-depth interviews with 18 teachers and 36 students. The findings reveal a three-level gap. First, the curriculum acknowledges ICC but lacks clear and measurable operational guidelines. Second, textbooks predominantly emphasize Anglo-American culture (64.8% of cultural content) while providing limited representation of Indonesian and global cultures. Third, 78.2% of teachers reported not explicitly integrating cultural dimensions into English instruction, resulting in stereotypical and culturally limited classroom practices. To address these issues, the study proposes the Triangulated Cultural Literacy (TCL) framework, integrating reflection on learners’ own culture, balanced exploration of target cultures, and intercultural negotiation. The findings highlight the need to operationalize ICC in the curriculum, improve textbook cultural representation, and strengthen teachers’ intercultural pedagogical competence.